A New Method for Optimizing the Cabin Layout of Manned Submersibles. (4th December 2020) - Wang, Wenzhong; Zhang, Shusheng; Ye, Cong; Chen, Dengkai; Fan, Hao
Abstract : In order to reduce the misoperation of submersible pilots in the complex environment of deep sea and improve human reliability, it is a very important method to optimize the cabin space of manned submersible. In this paper, manned submersible Jiaolong is taken as an example to describe the breakthrough of traditional modes for optimizing the cabin layout of manned submersible with an aesthetic perspective of deconstruction and reconstruction thinking; the layout is optimized based on deconstruction and reconstruction from the cultural perspective of interdisciplinary. The experimental results show that the layout of manned submersible cabin is optimized by combining the theory of deconstruction and reconstruction aesthetics and human factors engineering, and the feasibility and effectiveness of this method are verified by multiobjective genetic algorithm. Deconstruction and reconfiguration layout optimization improves the human reliability of divers. It is a new method for the optimization of manned submersible cabin layout and also provides a reference for studies on the layout of similar small space.